The Use of Taboo Game to Develop Students’ Vocabulary Mastery - Fali, Muhammad; Rofiqoh, Rofiqoh; Patmasari, Andi; Suriaman, Aminah (Journal of English Language and Education, 2026)
Taboo Game is a word guessing game that challenges players to describe target words without using related forbidden words. This research aims to prove whether the use of Taboo Game can develop English vocabulary mastery of the tenth-grade students at SMA Negeri 1 Parigi Tengah. This quasi-experimental study used purposive sampling, dividing 54 students into experimental and control groups. The experimental group received vocabulary instruction through Taboo Game, while the control group used conventional methods. Data were collected through pre-tests and post-tests. Results showed significant differences between groups, with the experimental group achieving a mean post-test score of 81.11 compared to the control group's 76.96 (sig 0.05). The experimental group demonstrated an average improvement of 13.48 points. These findings confirm that Taboo Game is an effective strategy for developing vocabulary mastery, creating more engaging learning experiences for students across various proficiency levels.